ChemInform Abstract: One‐Pot Preparation of 3‐Chloropiperidine Compounds via Cu(II)‐Promoted Intramolecular Chloroamination of Unfunctionalized Olefins. Issue 47 (4th November 2013) - Li, Run‐Lin; Liu, Gong‐Qing; Li, Wei; Wang, Yu‐Mei; Li, Lin; Duan, Lili; Li, Yue‐Ming
Abstract The CuCl2 promoted cyclization of unsaturated amines at room temperature leads to the formation of intermediate pyrrolidine derivatives, which rearrange at elevated temperature to produce piperidines.